Differences In The Effect Of Plyometric Exercise Front Jump And Side Jump Against The Explosion Of Limbs In The Volleyball - Dio Leowanda; Ronni Yenes (Performa, 2019)
Based on the experience of researchers while practicing training at the Semen Padang club, the causes of athletes do not have a good jump. One of them is the physical ability of leg muscle explosive power. This type of research is quasi-experimental, this study aims to determine the differences in the effect of Plyometric Exercise Front Jump and Side Jump Against the Explosion of Limbs in the Volleyball Athlete's Son Semen Padang Junior U-18. This research was conducted in June to July 2019 in Semen Padang Padang. The sample in this study were 12 athletes, the data analysis technique used the t test. Based on data analysis in this study using the T-Test. The results of data processing in this study are 1) obtained tcount (7.19) > ttable (2.57), meaning that the application of the front jump method can increase leg muscle explosive power, 2) obtained tcount (7, 43) > ttable (2, 57), meaning that the application of the side jump method can increase leg muscle explosive power, 3) obtained tcount (0.33) < ttable (2.57), meaning that the application of the front jump method and the side jump method can both increase the leg muscle explosive power, where the side jump method shows better results in increasing leg muscle explosive power.